Dynamic Optimization of Autocatalytic Esterification in Semi Batch Reactor using Orthogonal Collocation and Control Vector Parameterization Method - F.S. Rohman, F.S. Rohman; S. A. Sata, S. A. Sata; N. Aziz, N. Aziz (2011)
Catalyzed Esterification of Propionic Anhydride with 2-Butanol is commonly applied in semi batch reactors where the process variables undergo significant changes during the duration of the batch. In this semi batch operation, there is no steady state and thus no constant setpoints around which the key variables can be regulated.